Disabled Shooting Project (2022)
We welcome ALL disabilities into this competitive mainstream sport, as well as helping less-able shooters to stay in it. Target shooting is the most accessible, inclusive and integrated of all mainstream sports - this is the Disabled Shooting Project's key message. Our role is to help as many people as possible to enjoy this great sport, either by helping them into it, or by helping them to stay in it.